Peningkatan Kemampuan Pendidik Sebaya melalui Pelatihan Model Pembelajaran JIGSAW dan Penggunaan Modul Seksualitas Berbasis Agama Islam di Pusat Informasi dan Konseling Remaja SMP Kota Padang - Alsri Windra Doni; Dewi Susanti; Neni Fitra Hayati (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2023)
Increasing the abilities of peer educators through jigsaw learning model training and the use of Islamic religion-based sexuality modules at the Padang City Middle School Youth Information and Counseling Center is an activity carried out by implementing the jigsaw cooperative learning model and Islamic religion-based sexual education modules for teenagers. The aim of this activity is to increase the abilities of peer educators through training in the jigsaw learning model using an Islamic religion-based sexuality module at the Youth Information and Counseling Center in Padang City. The method of this activity is to carry out advocacy activities, provide training, carry out monitoring and evaluation and dissemination by providing Islamic religion-based sexual education modules for peer educators in the PIK-R room in Padang City. Based on the results of the activity, it is known that peer educators' knowledge about sexual behavior has increased, especially in terms of knowledge about teenagers, the etiquette of men and women in everyday life according to the Islamic religion. It is hoped that this will continue to be applied in everyday life so that it becomes a habit and avoids sexually transmitted diseases and does not add to our sins as religious people, where adolescence is often associated with myths and stereotypes about deviance and impropriety. Conclusion: it is necessary to apply learning about Islamic religion-based relationships to today's teenagers so that they are not influenced by outside cultures.